Reduction of the number of faults caused by lightning for transmission line - Dinh Chung Phan (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, author proposed an algorithm to determine method which is used to reduce the fault number caused by lightning on a transmission line. The algorithm is developed based on three methods including increase in the insulator string length, surge arrester installation, and surge arrester installation in combination with increase in the insulator string length. The output of algorithm is the proposed method which makes the number of faults caused by lightning satisfy the requirement and its investment is the cheapest in them. Based on this algorithm, the reasonable method (the number of tower positions needing to improve) to reduce the number of lightning caused faults of the transmission line can determine if we know the ratio of the required number lightning caused faults to the current value. This algorithm is applied to a transmission line to propose an improving method so that the fault number satisfies the requirement. This algorithm is implemented to a 220kV transmission line. The calculation results show the reasonable method and it also indicates in detail which towers should install surge arrester, which towers should increase the insulator string length.